If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18-(1/22)(2x)=9-(1/22)(x)
We simplify the equation to the form, which is simple to understand
18-(1/22)*(2x)=9-(1/22)*(x)
Reorder the terms in parentheses
multiplication of parentheses
18-( + 0.090909090909091x)=9-( + 0.045454545454545)*(x)
Remove unnecessary parentheses
18-0.090909090909091x=9-( + 0.045454545454545)*(x)
Reorder the terms in parentheses
multiplication of parentheses
18-0.090909090909091x=9-( + 0.045454545454545x)
Remove unnecessary parentheses
18-0.090909090909091x=9-0.045454545454545x
We move all terms containing x to the left and all other terms to the right.
-0.090909090909091x + 0.045454545454545x=+9-18
We simplify left and right side of the equation.
-0.045454545454546x=-9
We divide both sides of the equation by -0.045454545454546 to get x.
x=198
| (4x+5)(5x-1)=0 | | 2x+0.5x=770 | | log^2(x-1)=4 | | (2/3)(x+4)=(3/8)(x-3) | | 3x-8=4x-25 | | 6.1w+2.2=0.5w-3.4 | | 950+800+3x=800+300+8x | | (4n+18)+(5n+27)=180 | | 3200=8x+4x^2 | | .50x+.05(130)=.25(66) | | 0.36x+026=3.86 | | 6x=13-3y | | 20x+5=21x-6 | | 2(x-2)=5x+12 | | 5x+25y=10 | | h(x)=2x^2-12+18 | | (3/4)y-(1/4)=(5/4)y+(1/8) | | 4(p-1)=5p+3p-8(2p+2) | | 4x+76x=37 | | log^3(14x-3)=log^3(6x+5) | | -5x-12=-8x | | 2x+4=-12x+14 | | 8a+6=76 | | -4x-3=-4x+4 | | x^2+50x=21279 | | (5x^2+6x+12)=0 | | Letq=180 | | a=2pir^2h | | x^2+50x=6600 | | -3x+8=-3x | | 6x+4=-2+28 | | 8y-3=3y-2+4y |